Multifunctional Polymeric Micelles for Combining Chelation and Detection of Iron in Living Cells - Liu, Zhi (Adv Healthc Mater, 2017)
Multifunctional self-assembled micelles composed of Pluronics F127 polymer chains are developed and investigated for chelation and selective detection of iron(III) in vitro and in iron-overloaded cells. Tetraphenylethene (TPE) is encapsulated into the micelle core and the iron chelate drug deferoxamine (DFO) is conjugated to micelles to generate a fluorescence quenching detection system termed DFO-TFM for short, where T stands for TPE, F for F127, and M for micelle. The key to the successful formation of this fluorescence quenching system is due to the near-ideal overlap between the absorption spectrum of the DFO:iron(III) complex and fluorescence spectrum of TPE. DFO-TFM can retain the iron-chelation properties of DFO and exhibits negligible cytotoxicity compared to free DFO. Furthermore, this fluorescence “turn-off” system can be utilized to detect the presence of iron and to monitor the chelation process in an iron overload cell model. This study serves as an effective proof-of-concept model for designing future in vivo systems capable of combining the features of iron chelation with iron detection and efforts toward the development of such detection systems are currently underway.